Estimation of left ventricular function in chronic alcoholics - Sindhya, K. S.; S., Arthi P. (International Journal of Advances in Medicine, 2021)
Background: Alcohol abuse is one of the leading causes of millions of deaths, it is also a burden in society. Direct toxicity of ethanol affects cardiac muscle Acute intoxication shows pathological electrocardiogram changes such as sinus tachycardia in alcohol dependence syndrome, sinus arrhythmias, prolongation of QT interval, ventricular polarising complexes, poor progression of R wave, torse de pointes. Changes found in echocardiography are alteration in septal and ventricular wall thickness, left atrial dimensions, left ventricle dimension and mass. Methods: Patients attending outpatient and inpatients section in our tertiary care hospital Shri Balaji Vidhyapeet University were considered in study for a period of two years. Study size was 85 patients, Data were collected regarding proportion of ethanol intake, history of duration, symptoms related to cardiovascular system, blood parameters including thyroid function test, blood sugars are done, body mass index calculated, blood pressure recorded master chart made for statistical verification. The three-dimensional echocardiography in M mode is done by our cardiologist. Results: Echocardiography findings were correlated with duration of intake of alcohol end diastolic volume index (EDVI), End systolic volume index (ESVI), Left ventricle mass index (LVMI) had positive correlation of p-value less than 0.05. when quantity of ethanol intake correlated with echocardiography, Left ventricular inner dimension (LVID), fractional shortening (FS), ejection fraction (EF), posterior wall thickness, E/A ratio has no significance with p value. Abnormality is noted in left ventricle diastolic function and is corresponded to quantity and duration of alcohol. Moderate amount of less than 150grams of ethanol did not showed toxic effects in heart while severe quantity and duration more than ten years of intake showed left ventricle dysfunction Conclusions: Ethanol consumption in massive amount impair cardiac contractile function. Change in left ventricle volume takes place before the defect in the ventricular filling, which would be a marker for effect of ethanol in heart.